Understanding the Psychological Impacts of Teenage Pregnancy through a Socio-ecological Framework and Life Course Approach - Tebb, Kathleen P.; Brindis, Claire D. (Seminars in Reproductive Medicine, 2022)
The relationship between mental health and teenage pregnancy is complex. Mental health can be both an antecedent and contributing factor to teenage pregnancy and a concurrent factor wherein pregnancy itself can contribute to depression. Expectant and parenting teens (EPT) are faced with the simultaneous challenges of pregnancy and parenting while navigating the developmental tasks of adolescence which increases their risk for mental health problems. In addition, adolescents growing up in stressful community or home situations where their parents experienced depression, further places them and their children at greater risk of repeated patterns over time. However, adverse mental health outcomes are not inevitable. The socio-ecological model combined with a life course perspective provides a framework for understanding the complexity of risk and protective factors at multiple levels that influence knowledge, attitudes, behaviors, and other health outcomes later in life and across generations. This approach has important implications for reducing adolescents' risk of an unintended/mistimed pregnancy and improving mental health and other outcomes for EPT. This paper describes the prevalence of mental health problems in EPT and using a socio-ecological framework and life course perspective explains variations in mental health outcome among EPT. Implications for interventions and innovative approaches are also discussed.
Keywords: expectant and parenting teens; mental health; socio-ecological model; life course; resilience